2009
DOI: 10.1080/01674820903049843
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward menstrual suppression and conformity to feminine norms in young and middle-aged Mexican women

Abstract: Seventy seven college students and 66 middle-aged Mexican women completed an adapted questionnaire of attitudes toward menstrual suppression and the Conformity to Feminine Norms Inventory. Participants showed a great interest in menstrual suppression, but few were familiar with this issue. Young women would like to have longer menstrual cycles than monthly and were more supportive of menstrual suppression than middle-aged women. Women who would prefer to have longer menstrual cycles showed less conformity to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…No studies were found that addressed ATMS and self‐objectification. However, the findings from the correlational analysis are in accordance with studies showing that higher scores on ATMS (Marvan & Lama ) and on SOQ (Brinkman et al . ) are related to traditional attitudes towards the feminine role.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…No studies were found that addressed ATMS and self‐objectification. However, the findings from the correlational analysis are in accordance with studies showing that higher scores on ATMS (Marvan & Lama ) and on SOQ (Brinkman et al . ) are related to traditional attitudes towards the feminine role.…”
Section: Discussionsupporting
confidence: 89%
“…The original instruments used in this study have all shown acceptable reliability and validity in various studies (McKinley & Hyde , Fredrickson & Roberts , Noll & Fredrickson , McKinley , Marvan et al . , Moradi & Huang , Marvan & Lama ). Permission to use all the instruments was gained from their authors.…”
Section: The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…These results might be because BS suggests that women should be protected and cared for because they are vulnerable and weak and that women ought to be placed on a pedestal, but only if they conform to women's traditional roles. For traditionally oriented women, menstruation is a vital part of a woman's life (Marván & Lama, ), and it is consistent with, and perhaps necessary to, their concept of themselves as wives and mothers (Miller & Smith, ). If we put these ideas together, one might assume that a woman who agrees with BS statements holds the stereotypical belief that the premenstrual and menstrual phases are characterized by weakness and disability; therefore, she might also believe that a menstruating or premenstrual woman needs protection from some daily activities and stresses.…”
Section: Discussionmentioning
confidence: 99%